2021
DOI: 10.1002/star.202100144
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Controlled Drug Release, and Cell Viability Evaluation of Tenofovir Alafenamide‐Loaded Chitosan Nanoparticles

Abstract: Tenofovir alafenamide (TAF) is used as a hepatitis B virus (HBV) nucleotide reverse transcriptase inhibitor for the treatment of chronic HBV infection. However, the use of TAF suffers from its poor solubility and low bioavailability. Therefore, this study prepared and characterized chitosan nanoparticles (CHS NPs) loaded with TAF. Morphological findings demonstrated that CHS NPs are roughly spherical and homogeneous in shape. Besides, TAF‐loaded CHS NPs displayed the hydrodynamic diameter, zeta potential, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
3
10
1
Order By: Relevance
“…However, none of the peaks of TAF appear in the FTIR of the drug-loaded nanoparticles. Similar results were reported by Ulu et al in their study where they proposed that the absence of peaks of TAF suggests that the drug was fully encapsulated within the nanoparticles and no possible interaction of the drug with the components of the nanoparticles was observed, which is why only the peaks of PEGylated chitosan nanoparticles were observed and the peaks of TAF were masked within the nanoparticle structure [ 29 ].…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…However, none of the peaks of TAF appear in the FTIR of the drug-loaded nanoparticles. Similar results were reported by Ulu et al in their study where they proposed that the absence of peaks of TAF suggests that the drug was fully encapsulated within the nanoparticles and no possible interaction of the drug with the components of the nanoparticles was observed, which is why only the peaks of PEGylated chitosan nanoparticles were observed and the peaks of TAF were masked within the nanoparticle structure [ 29 ].…”
Section: Resultssupporting
confidence: 85%
“…In the XRD diffractogram, the synthesized polymer had an amorphous nature, and the SEM results were authenticated with XRD where distinct or sharp peaks were observed. Ulu et al developed simple and drug-loaded chitosan nanoparticles and reported that the nanoparticles were roughly spherical in shape and evenly distributed [ 29 ]. The spherical shape of the nanoparticles was due to the tendency of chitosan molecules to fuse with each other with extensive hydrogen bonds in the structure [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations